Optimizing Methylammonium Lead Iodide Perovskite synthesis for solar cells via two-step spin coating with mixed solvents - Abdul Aziz, Ahmad Muhajer; Muniandy, Subathra; Imam Rifai, Malinda Noviasari; Idris, Muhammad Idzdihar; Mohammed Napiah, Zul Atfyi Fauzan; Shafie, Suhaidi; Rashid, Marzaini (Universiti Malaysia Perlis, 2024)
Methylammonium Lead Iodide (MAPbI3) has often been known to have a perovskite content and is widely employed in Perovskite Solar Cells (PSCs). However, PSCs suffer from rapid degradation due to their low stability and sensitivity to light, heat, humidity, and air. Hence, this project proposes a two-step spin coat method to synthesize MAPbI3 perovskites in an ambient condition using two different types of solvent (DMF only and a mixture of DMF and DMSO) which were prepared to examine the quality of the perovskite layer. The thin films were characterized to study the structural, optical properties, and surface morphology using XRD, UV-Vis spectroscopy, and SEM. The XRD results show that the perovskite layer prepared using a mixture of DMF and DMSO has a better crystallinity than DMF, even after the sample was kept for two days as the principal peaks confirm the complete formation of MAPbI3 perovskite film. UV-Vis showed that the perovskite layer prepared with the mixture of DMF and DMSO as the solvent has a higher absorbance than the perovskite layer prepared with DMF. The surface morphology of the MAPbI3 films consists of the formation of cubical crystals of uniform size with high compactness, as confirmed by the SEM analysis. However, after two days, both samples showed a degradation providing feedback on the occurred transition to PbI2 due to the contact with moisture and thermal stability. Moreover, the better stability of perovskite films was observed by a two-step than one-step process was demonstrated with comparatively good reproducibility.